2018
DOI: 10.1016/j.yfrne.2018.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and structural adaptations to stress

Abstract: Unpredictable aversive experiences, or stressors, lead to changes in depression- and anxiety-related behavior and to changes in hippocampal structure including decreases in adult neurogenesis, granule cell and pyramidal cell dendritic morphology, and volume. Here we review the relationship between these behavioral and structural changes and discuss the possibility that these changes may be largely adaptive. Specifically, we suggest that new neurons in the dentate gyrus enhance behavioral adaptability to change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 128 publications
3
50
1
Order By: Relevance
“…This is consistent with previous work showing that new neurons are activated by stress and hasten recovery of the stress response to acute stressors (Snyder et al, 2011). Taken together, these findings support the idea that new neurons enhance the ability to update behavior and adapt to new safer, contextual situations following a traumatic stressor, preventing generalization of anxiety from persisting beyond when it is adaptive (Cameron & Schoenfeld, 2018).…”
Section: Role Of Neurogenesis In Stress Effectssupporting
confidence: 91%
“…This is consistent with previous work showing that new neurons are activated by stress and hasten recovery of the stress response to acute stressors (Snyder et al, 2011). Taken together, these findings support the idea that new neurons enhance the ability to update behavior and adapt to new safer, contextual situations following a traumatic stressor, preventing generalization of anxiety from persisting beyond when it is adaptive (Cameron & Schoenfeld, 2018).…”
Section: Role Of Neurogenesis In Stress Effectssupporting
confidence: 91%
“…In animal studies, stress alters ensuing synaptic plasticity and firing properties of hippocampal neurons. Additionally, both human and animal studies have shown that stress can change neuronal morphology, suppress neuronal proliferation, alter hippocampal volume [44,45], and, perhaps alter the time course of hippocampal growth [46]. Varying levels of hypothalamic-pituitary-adrenal axis neuroendocrine hormones, particularly glucocorticoids, appear to mediate the myriad stress effects on the hippocampus [45].…”
Section: Discussionmentioning
confidence: 99%
“…However, an increase in the expression of pERK1 and pERK2 in the hippocampus has been detected only in defeated adult mice (Pardon et al., ). This activation of pERK1/2 and CREB in the DG might generate behaviors similar to depression or anxiety (Cameron & Schoenfeld, ; Gass & Riva, ). These results may throw light on the relationship of modifications of dopaminergic neurotransmission in the reward circuit (Nikulina, Lacagnina, Fanous, Wang, & Hammer, ; Xu et al., ; Yang et al., ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%